(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Cognitive development entails more than maturation of thechild’s brain. Cognitive development is the product of the child’s attempts to understandthe family, neighborhood, school and the world at large during the period ofrapid brain growth and learning. Hearing loss is linked to a faster cognitivedecline and cognitive impairment. The effects of deafness on cognitivedevelopment are, therefore, quite diverse and complex due to the multitudinousways in which families, societies, and cultures, react to and interact withchildren who are born deaf and hence do not spontaneously learn to talk andcomprehend speech. In this paper, an attempt has been made to investigate theattitude of parents of hearing impaired children and parents of normal childrentowards their children.